GEOLOGICAL AND GEOPHYSICAL STUDY OF THE ASSAKEAUDEN TROUGH - Khaitov O G,; Bekmanov N. U, (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the oil and gas prospecting work carried out within the territory in question, systematic solution of problems of different nature and geological research, the results of which served as material for the state geological map and an explanatory note to it. The following anticlines distinguished Shakhpakhta anticline, Central Ustyurt and Muzbel anticlinal zones, Aibugir and Shorji anticlines, Assakeudan and Barsakelmes troughs.